Plano Municipal de Educação de Sorocaba/SP: monitoramento, avaliação e controle social - Almenara, Gilsemara Vasques Rodrigues (2024)
The objective of this research in education policy and management areas was to analyze the debates and clashes in the light of the instances responsible for monitoring and evaluating the PME (Municipal Education Plan) of Sorocaba/SP, regarding the monitoring flow, evaluation flow and referrals for correction of the goals set out in the document (PME), based on the dimension of social control, in the period 2015-2020. The PME was a requirement of the National Education Plan - Law No. 13,005, of June 25, 2014 (Brazil, 2014), which specifies, in Article 8, the requirement of elaboration and / or adequacy of the Municipal Education Plans within one year, counted from this law, which approved the National Education Plan (2014 - 2024), and which determined as the responsibility of the states and municipalities to elaborate respectively their plans in a democratic way, in order to ensure the effective participation of society. The research was limited to the period 2015-2020. The methodology was developed through qualitative research, consisting of bibliographic and documentary analysis and interviews based on a semi-structured script of questions. Data treatment was performed through content analysis, based on Bardin (1977). Three actors contributed to the data collection (03), being a component of the Technical Support Team of the PME, a member of the Permanent Education Forum and a member of the Municipal Council of Education. The results show that: the municipality of Sorocaba did not carry out its biennial stages of Monitoring and Evaluation of the PME, which directly affects the quality of public educational policies and the quality of education. Keywords: Municipal Education Plan; Monitoring and Evaluation; Social Control; Sorocaba/SP.